Editor’s Note - Fogg, Thomas (Current Musicology, 2014)
The Acknowledgment—in which this note is, at least in part, an exer-cise—is a tricky genre: there are always too many people to thank but too few words fit for the task. A game presents itself: to avoid where possible repetitions of the golden word—the T–word—and its few synonyms; in other words, no thanks, no gratitude. Keith Richards (2010, 549), in his autobiography Life, has a tidy solution: a single “my thanks to . . .” and then two sober columns of alphabetically ordered names. Similarly, in one of the more moving exemplars, Roger Parker (2006, xi–xii) follows “thanks to . . .” with a sentence almost two pages long, where he honors each addressee with a personalized vignette held between semicolons. With tongue presumably in cheek, Tamara Levitz (2012, xvii) interrupts the steady toll of T–words when, rather than thank her proofreaders, she “thinks” them.